If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 10 = 4t + 5 Reorder the terms: 10 + 3t = 4t + 5 Reorder the terms: 10 + 3t = 5 + 4t Solving 10 + 3t = 5 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 10 + 3t + -4t = 5 + 4t + -4t Combine like terms: 3t + -4t = -1t 10 + -1t = 5 + 4t + -4t Combine like terms: 4t + -4t = 0 10 + -1t = 5 + 0 10 + -1t = 5 Add '-10' to each side of the equation. 10 + -10 + -1t = 5 + -10 Combine like terms: 10 + -10 = 0 0 + -1t = 5 + -10 -1t = 5 + -10 Combine like terms: 5 + -10 = -5 -1t = -5 Divide each side by '-1'. t = 5 Simplifying t = 5
| -7y+7-6=-14y+6-4 | | (-8.946)(14.08)= | | 5x+8=41 | | equals= | | X^3+7x^2=x^2+16x | | n=3/4 | | (X^3)+(3x^2)-8x=0 | | y=(3/5*-2)-2/3 | | y=3/5×-2-2/3 | | 9x-7=6-4+5 | | (-12/47)(-47/24)= | | (-12/47)(-47/12)k= | | (16x)^(1/2) | | 5x+(-5+9)=-3 | | 16x+8y=85 | | x^2y-x^2+16y=0 | | (16-2x)(12-2x)=96 | | h=-0.44t^2+2.2t+10 | | y=-.6*55+22 | | y=-0.6*45+22 | | g(x)=4x^3 | | y=-.06*35+22 | | a^2-2a=100 | | y=-0.6*25+22 | | 1-4/x=2 | | 3+6s-2=6s+3-2s | | 6/(11y-1)=3/(5y-1) | | 5x/9=(x-5)/45 | | (w-y/2)(2) | | 9x+1=5x+11 | | (X-0.1)+1= | | 2y(4-2)=2/2 |